An autopsy case of progressive supranuclear palsy. Pallido‐nigro‐luysian type with argyrophilic grains clinically presenting with personality and behavioral changes. Issue 5 (10th July 2022) - Suzuki, Yuki; Adachi, Tadashi; Sakuwa, Mayuko; Sakata, Ryoichi; Takigawa, Hiroshi; Hasegawa, Masato; Hanajima, Ritsuko
Abstract : Pallido‐nigro‐luysian atrophy (PNLA) is a variant of progressive supranuclear palsy (PSP). Patients with PSP sometimes show psychiatric signs, but there are few reports about such signs being associated with PSP‐PNLA. Here, we report a case of PSP‐PNLA with argyrophilic grains (AGs) in a patient clinically diagnosed as having PSP‐frontotemporal dementia (PSP‐F). A 74‐year‐old man described as "kind" presented with impaired memory, irritability, and apathy. He showed levodopa‐resistant parkinsonism and postural instability. Brain magnetic resonance imaging revealed mild atrophy of the midbrain and right‐side‐dominant atrophy of the hippocampus and temporal lobe. The patient was diagnosed as having PSP with frontal lobe cognitive or behavioral presentations (PSP‐F). He died of aspiration pneumonia at age 81. At autopsy, macroscopic examination revealed depigmentation of the substantia nigra and grayish discoloration of the dentate nucleus, globus pallidus, and subthalamic nucleus. Severe gliosis was observed in the same regions. There were many phosphorylated tau‐immunoreactive equivocal tufted astrocytes in the globus pallidus. Many neurofibrillary tangles and neuropil threads were observed in the substantia nigra and subthalamic nucleus, and few tau aggregates were observed in the frontal cortex. In contrast, AGs were abundant in the amygdala, entorhinal cortex, and anterior cingulate gyrus, with an asymmetric distribution. The pathological observations led us to change the diagnosis to PSP‐PNLA with AGs. Although most cases of PSP‐F derive from tau pathology in the frontal cortex, this patient did not have phosphorylated tau‐immunoreactive aggregates in that location. Our observations suggest that the psychiatric signs of PSP‐F should be considered as being due to the presence of limbic AGs, not frontal tau pathology.